Evaluation of nitrogen and potassium uptake and efficiency of two rice varieties cultivated on an acid soil - Mohd Yusob, Shajarutulwardah; Ahmed, Osumanu Haruna; Wan Yahaya, Wan Asrina; Nik Ab. Majid, Nik Muhamad (Science Publications, 2007)
A pot study was carried with the following objectives: (i) To investigate N and K uptake of MR 220 and ARC 2 rice varieties grown on Bekenu series (Tipik Tualemkuts), and (ii) To investigate N and K use efficiency of MR 220 and ARC 2 grown on Bekenu series. Treatments evaluated were: (i) MR 220 and ARC 2 under fertilized condition (T1), and (ii) MR 220 and ARC 2 under unfertilized condition (T0). The experiment was conducted in a glasshouse at Universiti Putra Malaysia Bintulu Campus, Sarawak, Malaysia. Altogether 24 pots were used having a completely randomized design (CRD) with 6 replications (for each treatment and each variety). Nitrogen and K were applied in the forms of urea (46 % N) and muriate of potash (60 % K2O) for the two varieties. For T1 of MR 220, N, K, and P were applied at the rates of 4.0 g N, 1.10 g K2O and 2.13 g P2O5 per pot, respectively in split. In the case of T1 of ARC 2, N, K, and P rates used were 1.30 g N, 0.8 g K2O, and 1.70 g P2O5 per pot, respectively in split. At 65 days (ARC 2) and 70 days (MR 220) after planting, plants were sampled and partitioned into roots and stem, and their dry weight, N, and K concentrations determined using standard procedures. Soil sampling was done before and after fertilization. Soil total N was determined using the Kjeldahl method while exchangeable K, Ca, Mg, and Na were extracted by the double acid method and their concentrations determined by atomic absorption spectrophotometry. The dry ashing method was used for the determination of K, Ca, Mg and Na concentrations in plant tissues while the Kjeldahl method was used to determine total N in plant tissues. The concentrations multiplied by the oven dried weight of roots and stem provided N, K, Ca, Mg and Na uptake in these plant parts. The N and K use efficiency was then calculated using the subtraction method. With the exception of Ca, urea and KCl application significantly increased soil N, K, Mg, and Na concentrations. Application of K fertilizer significantly increased soil exchangeable K under MR 220 and ARC 2 cultivations. But this accumulation did not reflect in plant height, number of panicles, dry matter production, K uptake and K use efficiency. Urea application significantly increased N concentration in both roots and stem of MR 220 but the significant effect of N uptake reflected in stem only. Urea application however, did not affect N accumulation, plant height, number of panicles, and dry matter production. Nitrogen use efficiency was also low. As the results showed inefficient nutrient use, series of trials on Bekenu series on the interaction between inorganic and organic fertilizers (e.g. compost) should be carried out as this is likely to improve the inherent low exchange properties of this soil which partly contributes to poor fertility properties.